2020
DOI: 10.1186/s12889-020-09639-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and mortality in the general population: a systematic review and meta-analysis

Abstract: Background Quality of life (QoL) is multi-dimensional concept of an individual’ general well-being status in relation to their value, environment, cultural and social context in which they live. This study aimed to quantitatively synthesise available evidence on the association between QoL and mortality in the general population. Methods An electronic search was conducted using three bibliographic databases, MEDLINE, EMBASE and PsycI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 81 publications
5
72
0
3
Order By: Relevance
“…The evidence on physical functioning scales such as the physical component summary score from SF-36 is more limited; a recent meta-analysis of four studies with a mean follow-up of 1.8 years showed better scores to be associated with lower mortality risk (odds ratio for 1 unit increase: 0.95). 40 In our study, both of these selfreported measures were associated with mortality, irrespective of the age at assessment. As with the objective measures of motor function, the hazard ratios of associations with mortality were higher when selfreported function was assessed closer to death.…”
Section: Comparison With Previous Studiessupporting
confidence: 49%
See 1 more Smart Citation
“…The evidence on physical functioning scales such as the physical component summary score from SF-36 is more limited; a recent meta-analysis of four studies with a mean follow-up of 1.8 years showed better scores to be associated with lower mortality risk (odds ratio for 1 unit increase: 0.95). 40 In our study, both of these selfreported measures were associated with mortality, irrespective of the age at assessment. As with the objective measures of motor function, the hazard ratios of associations with mortality were higher when selfreported function was assessed closer to death.…”
Section: Comparison With Previous Studiessupporting
confidence: 49%
“…The association of self-reported measures of motor function with mortality has mostly been examined using limitations in ADL in older adults, in whom it has a robust association with mortality,373839 with follow-up ranging from one to >15 years. The evidence on physical functioning scales such as the physical component summary score from SF-36 is more limited; a recent meta-analysis of four studies with a mean follow-up of 1.8 years showed better scores to be associated with lower mortality risk (odds ratio for 1 unit increase: 0.95) 40. In our study, both of these self-reported measures were associated with mortality, irrespective of the age at assessment.…”
Section: Discussionsupporting
confidence: 38%
“…Our study has certain strengths. Principally, to the best of our knowledge, it is one of the few studies which assesses the association of levels of PA and three important clinical outcomes, shown to be predictors of mortality among older adults in community dwellings [ 14 , 15 , 16 ]. Secondly, the instrument used for the assessment of HRQoL was a validated questionnaire, suitable for the population under study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we aimed to assess the association between these cut-off points relating to the amount of PA (≥600 MET-min/week) with three important health-related outcomes, that have recently been shown to be independent predictors of mortality among older adults in community dwellings [ 14 , 15 , 16 ], namely, sarcopenia [ 14 ], cardiovascular risk factors [ 15 ], and HRQoL [ 16 ]. The hypothesis that we formulate is the existence of a significant association between suitable levels of PA and a lower risk of sarcopenia and cardiovascular risk factors, as well as better HRQoL among elderly people in community dwellings in Lebanon.…”
Section: Introductionmentioning
confidence: 99%
“…An unhealthy lifestyle pattern was considered as an aggregate accounting the five unhealthy habits: smoking, absence of consumption of raw nuts, unhealthy dietary habits considered as the consumption of ultra-processed products such as pastries or carbonated beverages according to the Mediterranean dietary pattern adherence questionnaire, absence of reported specific weekly time devoted to physical activity and sleeping time less than 7 h. These habits were selected according to previous evidence showing the association of these factors with the development of chronic diseases, mainly in the European population. Moreover, these items are part of the validated Mediterranean dietary pattern adherence questionnaire as well as the GPAQ [7,26]. The association between SF-36 subscales and summaries and habits was assessed in both univariate and multivariate analysis, adjusted by age, sex, physical and mental comorbidities.…”
Section: Methodsmentioning
confidence: 99%